Rice Gene Index: A comprehensive pan-genome database for comparative and functional genomics of Asian rice - Yu, Zhichao; Chen, Yongming; Zhou, Yong; Zhang, Yulu; Li, Mengyuan; Ouyang, Yidan; Chebotarov, Dmytro; Mauleon, Ramil; Zhao, Hu; Xie, Weibo; McNally, Kenneth L.; Wing, Rod A.; et al. (Elsevier, 2023)
Asian rice (Oryza sativa) is the staple food for half the world and is a model crop that has been extensively studied. It contributes ∼20% of calories to the human diet (Stein et al., 2018). With the increase in global population and rapid changes in climate, rice breeders need to develop new and sustainable cultivars with higher yields, healthier grains, and reduced environmental footprints (Wing et al., 2018). Since the first gold-standard reference genome of rice variety Nipponbare was published (International Rice Genome Sequencing Project, 2005), an increasing number of rice accessions have been sequenced, assembled, and annotated with global efforts. Nowadays, a single reference genome is obviously insufficient to perform the genetic difference analysis for rice accessions. Therefore, the pan-genome has been proposed as a solution, which allows the discovery of more presence-absence variants compared with single-reference genome-based studies (Zhao et al., 2018). Over the past years, several databases, such as RAP-db (https://rapdb.dna.affrc.go.jp), RGAP (http://rice.uga.edu), and Gramene (https://www.gramene.org), have long-term served rice genomic research by providing information based on one or a series of individual reference genomes. To integrate and utilize the genomic information of multiple accessions, we performed comparative analyses and established the user-friendly Rice Gene Index (RGI; https://riceome.hzau.edu.cn) platform. RGI is the first gene-based pan-genome database for rice